Selectivity of Ca2+ channel blockers for dilator actions on the isolated lower esophageal sphincter and aorta from rats - Akira Takahara; Shuhei Nozaki; Akane Ishiguro; Kaori Okamura; Xin Cao; Megumi Aimoto; Yoshinobu Nagasawa (Elsevier, 2018)
We compared dilator actions of representative four Ca2+ channel blockers on the isolated lower esophagus sphincter (LES) and thoracic aorta from rats. Verapamil, diltiazem, nifedipine and cilnidipine suppressed KCl-induced contractions of LES and thoracic aorta in a concentration-dependent manner. The order of selectivity for LES, which was calculated as ratio of IC50 value for thoracic aorta divided by that for LES, was diltiazem > verapamil > nifedipine > cilnidipine. These results suggest that diltiazem more preferentially dilates the LES whereas cilnidipine is expected to have lower potential risk of gastroesophageal dysfunction during the antihypertensive therapy. Keywords: Ca2+ channel blockers, Lower esophagus sphincter, Thoracic aorta